Human Cholangiocytes Form a Polarized and Functional Bile Duct on Hollow Fiber Membranes - Wang, Zhenguo; Faria, João; van der Laan, Luc J. W.; Penning, Louis C.; Masereeuw, Rosalinde; Spee, Bart (Frontiers in Bioengineering and Biotechnology, 2022)
Liver diseases affect hundreds of millions of people worldwide; most often the hepatocytes or cholangiocytes are damaged. Diseases of the biliary tract cause severe patient burden, and cholangiocytes, the cells lining the biliary tract, are sensitive to numerous drugs. Therefore, investigations into proper cholangiocyte functions are of utmost importance, which is restricted, in vitro, by the lack of primary human cholangiocytes allowing such screening. To investigate biliary function, including transepithelial transport, cholangiocytes must be cultured as three-dimensional (3D) ductular structures. We previously established murine intrahepatic cholangiocyte organoid-derived cholangiocyte-like cells (CLCs) and cultured them onto polyethersulfone hollow fiber membranes (HFMs) to generate 3D duct structures that resemble native bile ducts at the structural and functional level. Here, we established an efficient, stepwise method for directed differentiation of human intrahepatic cholangiocyte organoids (ICOs) into CLCs. Human ICO-derived CLCs showed key characteristics of cholangiocytes, such as the expression of structural and functional markers, formation of primary cilia, and P-glycoprotein-mediated transport in a polarized fashion. The organoid cultures exhibit farnesoid X receptor (FXR)-dependent functions that are vital to liver bile acid homeostasis in vivo. Furthermore, human ICO-derived CLCs cultured on HFMs in a differentiation medium form tubular architecture with some tight, confluent, and polarized monolayers that better mimic native bile duct characteristics than differentiated cultures in standard 2D or Matrigel-based 3D culture plates. Together, our optimized differentiation protocol to obtain CLC organoids, when applied on HFMs to form bioengineered bile ducts, will facilitate studying cholangiopathies and allow developing therapeutic strategies.